Impairment of LA strain and LV myocardial work in Ph+ Chronic myeloid leukaemia patients treated with TKis. (4th February 2022) - Parlavecchio, A; Caminiti, R; Vetta, G; Pelaggi, G; Lofrumento, F; Vinciguerra, P; Parisi, F; Demurtas, E; Licordari, R; Cusma, M; Manganaro, R; Micari, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Worsening of cardiac function with increased arrhythmic risk is common in cancer patients undergoing chemotherapy. Impaired LV Global Longitudinal Strain (GLS) in these patients despite preserved ejection fraction is a common issue. Recently, myocardial work by speckle‐tracking echocardiography has been used to overcome GLS limitations in various conditions, but little is known about its usefulness in the detection of cardiac toxicity. Moreover, left atrial (LA) toxicity may occur early in the course of cancer therapy. The main aim of the study was to assess the cardiotoxic effects of tyrosine kinase inhibitors (TKIs) on patients with Philadelphia chromosome-positive chronic myeloid leukaemia (Ph+ CML) by using novel echocardiographic tools as myocardial work and atrial strain analysis. Methods: We retrospectively enrolled Ph+ CML patients treated with TKIs followed at the cardio-oncology outpatient clinic of our hospital from December 2018 to March 2019 who underwent clinical evaluation with ECG and echocardiogram (TTE) before and after one year of treatment with TKIs. Healthy subjects were enrolled in the control group matched for gender, age and cardiovascular risk factors. Myocardial work was derived from the strain-pressure relation, integrating in its calculation the non-invasive arterial pressure. LA longitudinal strain (reservoir, conduit and booster) was obtained from an optimized apical 4‐chamber view of the LA. Results: The study recruited 32 patients in Ph+ CML group and 32 healthy controls. 39% of patients were treated with Imatinib, 29.3% with Nilotinib, 4.9% with Dasatinib and 4.9% with Ponatinib. Main results are detailed in the Table 1. At one-year follow-up there was a significant reduction compared to baseline in Global Constructive Work (2555.22 ± 564.33 vs 2119.31 ± 700.19; p = 0.0001), Global Work Efficiency (96.13 ± 1.90 vs 94.00 ± 2.96; p = 0.002) and Global Work Index (2340.75 ± 579.57 vs 1938.46 ± 680.23; p = 0.001), and a non-significant reduction in Global Wasted Work (p = 0.393). Regarding left atrial strain analysis at the one-year follow-up there was a statistically significant reduction in LA contractile strain (booster= 14.63 ± 1.408 vs 12.38 ± 1.581; p= 0.018). LA contractile strain reduction was also observed in the comparison with controls (12.38 ± 2.99 vs 14.91 ± 3.09; p = 0.009). Any other significant difference was detected between baseline and FU TTE data in the Ph+ CML group. Conclusions: New imaging methods for the study of cardiotoxicity provide an additional tool for early prediction of potential adverse effects of antineoplastic drugs. TKIs therapy leads to an impairment of atrial contractility, which can be detected by atrial strain e myocardial work analysis.